2018
DOI: 10.22266/ijies2018.1231.21
|View full text |Cite
|
Sign up to set email alerts
|

New Method Based on Priority of Heterogeneous Traffic for Scheduling Techniques in M2M Communications over LTE Networks

Abstract: Machine to Machine (M2M) communication is a technology for machines communicating with each other without human intervention. Long Term Evolution (LTE) and Long-Term Evolution-Advanced (LTE-A) cellular networks technologies provide the resources required for M2M communication. However, LTE is required to meet M2M communication requirements, such as power management and support for a large number of devices while maintaining the Quality of Service (QoS) requirements for these devices. Resource allocation or sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…eMBB and uRLLC. An improved licensed resources allocation is presented in [15][16][17][18][19] to enable improved sufficient capacity for users. The authors of [20] propose multi-user preemptive scheduling (MUPS) to enhance eMBB traffic spectral efficiency, response time, and reliability of uRLLC in conventional multiple-inputmultiple-output (MU-MIMO) transmission when they identify the trade-off between the performance of uRLLC and overall capacity of the network system.…”
Section: Related Workmentioning
confidence: 99%
“…eMBB and uRLLC. An improved licensed resources allocation is presented in [15][16][17][18][19] to enable improved sufficient capacity for users. The authors of [20] propose multi-user preemptive scheduling (MUPS) to enhance eMBB traffic spectral efficiency, response time, and reliability of uRLLC in conventional multiple-inputmultiple-output (MU-MIMO) transmission when they identify the trade-off between the performance of uRLLC and overall capacity of the network system.…”
Section: Related Workmentioning
confidence: 99%
“…However, the future IoT causes different challenges among them we can cite the security of communication and privacy of users. In this paper, we focus on the authentication that is a critical security mechanism that accords authorized user's access to a network [5]. It is observed that a LTE user device carries out two authentication steps to get access to the multimedia services and this increases authentication complexity and the terminal's energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, congestion can occur due to simultaneous authentication signaling messages from M2M devices [6][7]. If a large number of M2M devices in a group need to access the network at the same time, traditional authentication protocols (EPS-AKA or EAP-AKA) will suffer from a high signal overhead, leading to signaling, authentication and reduction of Quality of Service (QoS) of the network [8]. The reason is that each device must perform a complete AKA authentication procedure with the home authentication server, respectively.…”
Section: Introductionmentioning
confidence: 99%